Functionalized cationic [4]helicenes with unique tuning of absorption, fluorescence and chiroptical properties up to the far-red range. Issue 7 (19th April 2016) - Delgado, I. Hernández; Pascal, S.; Wallabregue, A.; Duwald, R.; Besnard, C.; Guénée, L.; Nançoz, C.; Vauthey, E.; Tovar, R. C.; Lunkley, J. L.; Muller, G.; Lacour, J.
Abstract : Unprecedented regioselective post-functionalization of racemic and enantiopure cationic diaza [4]helicenes is afforded. Abstract : Unprecedented regioselective post-functionalization of racemic and enantiopure cationic diaza [4]helicenes is afforded. The peripheral auxochrome substituents allow a general tuning of the electrochemical, photophysical and chiroptical properties of the helical dyes (26 examples). For instance, electronic absorption and circular dichroism are modulated from the orange to near-infrared spectral range (575–750 nm), fluorescence quantum efficiency is enhanced up to 0.55 (631 nm) and circularly polarized luminescence is recorded in the red (| g lum | ∼ 10 −3 ).